Scenario of haor vulnerabilities and other obstacles for sustainable livelihood development in Nikli upazila - Sharma, PK (Journal of the Bangladesh Agricultural University, 2011)
The study was carried out in haor areas situated in Nikli upazila under Kishoregong district to explore the socioeconomic vulnerabilities status of the people residing near deep haor areas and their dependency on its natural resources. Total 110912 local residents who depend on the wetland for their survival are poor, with an annual average per capita income Tk 3175, a literacy rate is 20.5%.Total cultivable land 17912.75 hectares, fallow land 1007.59 hectares; single crop 79.32% and double crop land 20.68%; land under irrigation 90%.This paper also sheds light on the status of livelihood using resources and face problems are barriers to sustainable livelihood development. There haor based alternative activity is fishing (20%) followed by duck rearing (3%), Beef fating (6.6%), The study find 71% households were found effectively landless of which about 55% were absolutely landless and 17% households were migrated and 78.9% haor households are suffered from food insecurity mainly because of landlessness, mono-crop cultivation, seasonal unemployment and natural calamities. The study suggests that the avenues for prospective coping strategies are to put a stop to existing leasing system of haor water bodies, making proper arrangements for creating alternative income generating activities throughout the year. Change the money lending system and taking preventives and curative measures for natural calamities. Keywords: Socioeconomic; Indicator; Sustainable livelihood; Climate change DOI: 10.3329/jbau.v8i2.7939 J. Bangladesh Agril. Univ. 8(2): 283-290, 2010